Greening of brick and tile production: an index to evaluate its environmental performance - Divino Miranda de Oliveira, Leandro [UNESP]; Girotto Rebelato, Marcelo [UNESP]; Maria Saran, Luciana [UNESP] (My University, 2023)
This work presents an index to evaluate the environmental performance of brick and tile manufacturing. The steps used were: 1) process study; 2) waste analysis; 3) determination of the potential impact of waste; 4) normalization of the potential impact; 5) comparative weighting among the potentials; 6) creation of the index. The index considers three parameters: the amount of waste produced, the disposal of waste, and the spatial dispersion of waste. The index was called CIRI (Ceramic Industry Rating Index) and was tested in a ceramic company. The field application showed that the waste that offered the highest environmental impact were gases generated from the burning of chips (30.850%), ashes generated from the burning of chips (30.483%), and steel drums (28.937%), which total of 90.27%. The CIRI index was 28.732%, which shows bad waste management. In view of the findings, two points must be considered: 1) the impacts generated by gaseous could be mitigated by companies by using technologies for drying tiles and bricks with a lower level of environmental impact; 2) entrepreneurs should be concerned about the fate given to the ashes because the dispose practiced is not environmentally correct. The index is useful for assessing the environmental impact of the brick and tile industry. It is useful for managers insofar as a proposal for process improvements. The novelty of this study lies in the index developed, which was designed to consider: the potential for environmental impact, the amount of waste, the spatial coverage, and the adequacy of waste disposal.
Keywords: Bricks and roof tale production; Ceramic industry waste; Environmental performance evaluation